(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the formation of the image of birds in fiction, their symbolic and semantic connotations, and how they have developed in a historical and cultural context. Bird images have performed certain ideological and aesthetic functions in different periods and places, from ancient mythological sources to modern literature. In particular, the image of birds expresses the concepts of freedom, hope, divinity, homeland, and love. The article also includes a comparative analysis of bird images in Eastern and Western literary traditions, highlighting their evolutionary changes in artistic thinking.